Time to resolution: A prospective evaluation from the Society for Fetal Urology hydronephrosis registry. Issue 3 (June 2017) - Zee, R.S.; Herndon, C.D. Anthony; Cooper, C.S.; Kim, C.; McKenna, P.H.; Khoury, A.; Herbst, K.W.
Summary: Introduction: The resolution rate of prenatal urinary tract dilation (UTD) has been documented in several retrospective studies. The present study analyzed prospective observational registry data, with the aim of determining time to resolution among patients prenatally identified with mild postnatal UTD. Materials and methods: A total of 248 subjects, from four centers, were prospectively enrolled from 2008 to 2015. Exclusion criteria included other anomalies ( n  = 69), fewer than two ultrasounds, and/or <3 months follow-up ( n  = 26). Resolution was defined as Outcome A (SFU 0) and Outcome B (SFU 0/1). Fisher's exact test, Mann–Whitney U or Kruskal–Wallis test and Kaplan–Meier were used for analysis. Results/discussion: The median follow-up for 179 ( n  = 137 males) subjects was 15 months (IQR 7–24), range 0–56 months. VCUG was performed in 100 (57%) and VUR identified in 15 (15%). There was no association with reflux and resolution ( P  = 0.72). For resolution assessment ( n  = 153), lower grades were likely to resolve and demonstrated a higher rate in the Outcome B classification. Time to resolution also favored lower grades, with the majority resolving within 2 years (Figure). Surgical intervention was performed in 14 (8%). It is interesting to note that regardless of grade of UTD, there was no difference in frequency of US or the time that RUS was first performed. Practitioners performed the first RUS of life within a narrow window ranging from 0.27 RUS/month for Grade 1 UTD to 0.30 RUS/month for Grade 4 UTD. It was speculated that this practice pattern occurrence likely reflected the deficiency in knowledge by primary care providers, and identified a potential opportunity for education. The SFU registry substantiates that the vast majority of patients will demonstrate transient UTD and most cases that do not resolve will improve within 2 years of life. This data could be used to further an evidenced-based approach towards the evaluation and management of prenatal UTD, as outlined in the multidisciplinary consensus statement for prenatal urinary tract dilation. Conclusions: This prospective registry confirms that the majority of prenatal UTD is transient, resolution occurs within the first 3 years of life, and most patients will not need intervention. Redefining SFU 1 as normal increased the resolution rate. A large proportion of patients were not evaluated with a VCUG, therefore impact of VUR could not be determined. Figure Kaplan–Meier curve depicting resolution for patients initially presenting with SFU Grade 1 (grey) or Grade 2 (black) hydronephrosis censored for follow-up and surgical intervention. At 6 months, the probability of resolution for both grades is 10%. At 2 years, the probability of resolution for Grade 1 is 71% and Grade 2 is 58%. At 2.5 years, the probability of resolution is 100% for Grade 1 and 72% for Grade 2.